Book review: Residential child and youth care in a developing world Volumes 1-4 By Tuhinul Islam and Leon Fulcher [Editors] - Jennifer Brooker (Scottish Journal of Residential Child Care)
Residential Child and Youth Care in a Developing World (2016 – 2020) is a unique insight into global residential child and youth care practice, which emphasises that the usually negative Western literature perspective that many of us read about is not the experience of the majority of those involved in care, whether as participants or workers. Rather, we are offered glimpses into residential care practices in geographies that are often unfamiliar and not often included in the surrounding discourse.